2013
DOI: 10.1095/biolreprod.113.109769
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of Vitrified-Warmed Bovine Oocytes with Rho-Associated Coiled-Coil Kinase Inhibitor1

Abstract: Cryotolerance of matured bovine oocytes is not fully practical even though a promising vitrification procedure with a ultrarapid cooling rate was applied. The present study was conducted to investigate whether recovery culture of vitrified-warmed bovine oocytes with an inhibitor (Y-27632) of Rho-associated coiled-coil kinase (ROCK) can improve the developmental potential after in vitro fertilization (IVF) and in vitro culture. Immediately after warming, almost all oocytes appeared to be morphological normal. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 50 publications
(55 reference statements)
5
38
0
Order By: Relevance
“…However, there are conflicting reports on the positive effect of L-carnitine on cryosurvival of bovine oocytes (Phongnimitr et al 2013). Incidence of multiple aster formation, a possible cause for low developmental potential of vitrified-warmed bovine oocytes (Hara et al 2012), can be inhibited by a short-term culture of the postwarming oocytes in the presence of Rho-associated coiled-coil kinase (ROCK) inhibitor, with a significantly higher blastocyst yield of 21% compared with 14% in untreated control (Hwang et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, there are conflicting reports on the positive effect of L-carnitine on cryosurvival of bovine oocytes (Phongnimitr et al 2013). Incidence of multiple aster formation, a possible cause for low developmental potential of vitrified-warmed bovine oocytes (Hara et al 2012), can be inhibited by a short-term culture of the postwarming oocytes in the presence of Rho-associated coiled-coil kinase (ROCK) inhibitor, with a significantly higher blastocyst yield of 21% compared with 14% in untreated control (Hwang et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Difference in multiple aster formation rate between fresh and stored ovary-derived oocytes was small despite of 210 the presence of significant difference (Fig. 2B) when compared to the difference described for vitrified-warmed oocytes with or without ROCK inhibitor treatment (Hwang et al 2013). Therefore, this may explain the failure of ROCK inhibition-mediated improvement in blastocyst yield from stored ovary-derived oocytes.…”
Section: Discussionmentioning
confidence: 81%
“…Therefore, treatment with the ROCK inhibitor may be useful to suppress the multiple aster formation by stabilizing astral structure. Hwang et al (2013) reported that ROCK inhibition-assisted suppression of multiple 205 aster formation in vitrified-warmed bovine oocytes led to a significant improvement of blastocyst yield from 14 to 21%. However in the present study, it may be reasonable to conclude that multiple aster formation is not directly involved in the developmental potential of bovine oocytes impaired by ovary storage (Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations